2018
DOI: 10.1073/pnas.1805348115
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic investigation of high-elevation adaptation in ectothermic snakes

Abstract: Several previous genomic studies have focused on adaptation to high elevations, but these investigations have been largely limited to endotherms. Snakes of the genus are endemic to the Tibetan plateau and therefore present an opportunity to study high-elevation adaptations in ectotherms. Here, we report the de novo assembly of the genome of a Tibetan hot-spring snake () and then compare its genome to the genomes of the other two species of , as well as to the genomes of two related species of snakes that occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
103
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(112 citation statements)
references
References 54 publications
5
103
2
2
Order By: Relevance
“…It might be attributed possibly to musk deer adaptation to the cold and highaltitude environment (1000-4200 m) where food sources and odorants are limited and diffused slowly, and the interactions between odorants and receptors weakened [79,80]. Similar results have been obtained in some high plateau animal genome studies, such as avian [81], wild boars [82], hot-spring snake [83] and Tibetan chicken [84]. Moreover, we observed 12 PSGs and 2 PSGs were involved in DNA damage and retinoid X receptor binding categories, respectively.…”
Section: Discussionsupporting
confidence: 74%
“…It might be attributed possibly to musk deer adaptation to the cold and highaltitude environment (1000-4200 m) where food sources and odorants are limited and diffused slowly, and the interactions between odorants and receptors weakened [79,80]. Similar results have been obtained in some high plateau animal genome studies, such as avian [81], wild boars [82], hot-spring snake [83] and Tibetan chicken [84]. Moreover, we observed 12 PSGs and 2 PSGs were involved in DNA damage and retinoid X receptor binding categories, respectively.…”
Section: Discussionsupporting
confidence: 74%
“…Both cold stress and strong UV radiation result in the oxidative stress due to generation of reactive oxygen species (ROS), such as hydrogen peroxide, superoxide anion, and hydroxyl radical (Halliwell, 2007;Wang et al, 2010;Lidon and Ramalho, 2011). Previous studies revealed that the DNA repair and radiation responses pathways may contribute to highland adaptation of the Crucihimalaya himalaica (Qiao et al, 2016;Zhang et al, 2019), Tibetan highland barley (Zeng et al, 2015), Tibetan antelope (Ge et al, 2013), Tibetan chicken (Zhang et al, 2016), and Tibetan hot-spring snake (Li et al, 2018). In the present study, we found that many outlier genes are involved in response to UV, DNA repair, response to ROS, and membrane lipid metabolic process.…”
Section: Scaffoldmentioning
confidence: 99%
“…Large numbers of endemic Tibetan species had developed unique morphological, physiological or genetic features to tolerate harsh living conditions (Wen 2014). Recent studies employing genome-wide approaches mainly focused on the hypoxia and metabolic adaptation of Tibetan terrestrial animals, such as wild yak (Qiu et al 2012), ground tit (Qu et al 2013), and Tibetan snake (Li et al 2018). Nevertheless, the draft genomes of very few Tibetan aquatic wildlife are sequenced (Liu et al 2019;Yang et al 2019), the genomic basis of aquatic animals adaptation to harsh water environments on the Tibetan Plateau still remain largely unknown.…”
Section: Introductionmentioning
confidence: 99%